Storytelling in Online Classes as an Oral Communication Strategy during the Covid-19 Pandemic - Cristie Ann L. Jaca (RIRAI Publisher, 2021)
The covid-19 pandemic has affected the students’ learning mentality as they become passive during online classes due to what is happening around them. The focus of teaching now is to make the students feel comfortable learning despite distractions caused by the pandemic. This paper presents storytelling as an oral communication strategy during online classes to be comfortable and motivated in their learning. This study used the descriptive research method that describes storytelling as an instructional strategy in online classes for students to be engaged and motivated to learn. The study's findings indicate that the use of stories and the act of telling personal stories have developed the students' expressive language and provided students the opportunity to express their ideas in a non-threatening environment. It proved that storytelling during the online class positively impacted the students’ oral communication skills. It helped students communicate their thoughts and feelings without fear of being judged. Moreover, it offered opportunities for students to participate in class.